Analysıs Of The Influence Of Webınar Educatıon On Knowledge About The Indonesıan Nurse Credentıal System In Cırebon Cıty - Dewi Erna Marisa; Santi Wahyuni; Holil Literature Wijaya; Saeful Bahri; Supriyadi Supriyadi; Devi Setiyana (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Based on PPNI's Membership Management Information System data, the number of members of the Cirebon City PPNI Regional Management Board recorded 1960 members who were collected in 11 Commissariat Management Boards Of all these nurses, there are still many who have joined so that they do not update their personal data on the grounds that they do not understand how to update the data which is ultimately related to their legality as. The purpose of this study was to analyze the effect of webinar education on nurses' knowledge of legal aspects and the Indonesian nurse credential system in Cirebon CityThe research method used is pre-experimental one group pretest - posttest design, using accidental sampling as many as 198 nurses who participated in the activity. Data collection was carried out by starting with the pre-test before the webinar and post-test after the webinar activity. The results of the study were analyzed by frequency distribution and then the normality test and Wilcoxon test were performed for bivariate analysis. The results showed that knowledge before treatment was the largest (62.6%) and treatment was the largest (51%) The results of the bivariate analysis showed a p-value of 0.000. The level of knowledge is greatly influenced by various things including age, educational background, workplace etc. The activity was conducive and followed enthusiastically by the participants, with material provided on STR and credentials which are important things for legality and nurse careers. The conclusion of this study is an increase in nurses' knowledge after being given education through webinars about legality and credentials